We have to solve this system of linear equations.
As we have the same coefficient for y, the most effective method to solve this is by elimination: we substract the first equation from the second one and then solve for x, as y is no longer part of this new equation.
We then substract the equations:
![\begin{gathered} (3x+7y)-(5x+7y)=11-9 \\ 3x-5x+7y-7y=2 \\ -2x+0y=2 \\ -2x=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3sjp2ps91d1fxute1epvusbxlgac5ufhkp.png)
Then, we can solve for x:
![\begin{gathered} -2x=2 \\ x=(2)/(-2) \\ x=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/654891tyubhekqdhu3u2648oc86undimb3.png)
Then, we can pick any of the two equations and, with the value of x = -1, we can solve for y as:
![\begin{gathered} 5x+7y=9 \\ 5(-1)+7y=9 \\ -5+7y=9 \\ 7y=9+5 \\ 7y=14 \\ y=(14)/(7) \\ y=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a7teh86nrgqmwdy49i2jx1ajnkedskp9k6.png)
Answer: x = -1 and y = 2.